2021
DOI: 10.1186/s40538-020-00205-4
|View full text |Cite
|
Sign up to set email alerts
|

Application of biochar-coated urea controlled loss of fertilizer nitrogen and increased nitrogen use efficiency

Abstract: Background The use of biochar-based N fertilizers have been considered among the most effective strategy for reducing nitrogen loss and improving nitrogen use efficiency (NUE). However, effect and mechanism of biochar-coated urea (BCU) controlling the loss of nitrogen from soil and NUE are rarely reported. Methodology In this study, a 65-d culture pot experiment of oilseed rape was used to investigate the impact of BCU on nitrogen leaching, ammonia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…(2015) Sawdust biochar Post Laboratory (leaching) experiment Higher water retention capacity Reduce nutrient leaching Gwenzi et al. (2018) Vinasse biochar Post Pot experimente Oilseed rape ( Brassica napus ) Reduced nitrate leaching Increased N concentration Increased NH 3 volatilization Increased Nitrogen use efficiency (NUE) by oilseed rape Jia et al. (2021) Acacia saligna and Jarrah sawdust biochar Post Pot experiment Wheat ( Triticum aestivum L. var.…”
Section: Effects Of Biochar-based Fertilizers On Soil Chemical Propertiesmentioning
confidence: 99%
“…(2015) Sawdust biochar Post Laboratory (leaching) experiment Higher water retention capacity Reduce nutrient leaching Gwenzi et al. (2018) Vinasse biochar Post Pot experimente Oilseed rape ( Brassica napus ) Reduced nitrate leaching Increased N concentration Increased NH 3 volatilization Increased Nitrogen use efficiency (NUE) by oilseed rape Jia et al. (2021) Acacia saligna and Jarrah sawdust biochar Post Pot experiment Wheat ( Triticum aestivum L. var.…”
Section: Effects Of Biochar-based Fertilizers On Soil Chemical Propertiesmentioning
confidence: 99%
“…The use of biochar-based N fertilizers (BBNFs) has been considered among the most effective strategy for reducing N loss and improving NUE (Liu et al 2019;Chen et al 2019a, b;Dong et al 2020). For example, Jia et al (2021) showed an increase in NUE by about 20% using BBNFs, when compared with urea. However, the preparation of BBNFs and their role in soil improvement and remediation, as well as their impact on plant growth and crop yield, have not been critically reviewed.…”
mentioning
confidence: 99%
“…Another point of view is that most biochar (especially straw biochar) itself is rich in Ca 2+ , K + , and Mg 2+ ions. With the entrance of biochar into the soil, exchange of these ions with H + and Al 3+ in the soil improved soil PH value [39] and thus promoted ammonia volatilization [17,40,41]. On the contrary, Mandal et al [42] have shown that biochar application at 0.5% and 2% decreases the ammonia volatilization by 36% and 48%, respectively.…”
Section: Discussionmentioning
confidence: 99%